(untitled) (Journal of Health Sciences, 2018)
Introduction: Shoulder pain is the most common form of extra-articular rheumatism. We aimed to determine the efficiency of the conventional physical treatment of the shoulder pain compared to the conventional treatment plus the Mulligan's joint mobilization technique and acupuncture. Methods: We included a total of 277 patients with the shoulder pain caused by adhesive capsulitis (frozen shoulder), calcific tendinitis, rotator cuff syndrome, or the tendinitis of the biceps muscle. We used clinical and radiological diagnostic criteria to make the diagnosis. Patients were assigned into group treated with conventional physiotherapy treatment during the ten days (CP)(n=148), and the group treated with conventional physiotherapy treatment plus the Mulligan joint mobilization and acupuncture (CP+MA)(n=128). Treatment efficiency was evaluated by assessing the status of the patients before and after the treatment with the Work Abilities and Activities of Daily Living (WAADL) scale as well as the Treatment Success scale. Results: Mean treatment duration was 13.36±5.83 and 10.86±4.55 days in CP and CP+MA group, respectively (p<0.05). Mean WAADL scores after the treatment were 3.98±1.04 and 4.61±1.10 in CP and CP+MA group, respectively (p<0.05). Mean Treatment success score was 3.16±0.74 and 4.35±0.78 in CP and CP+MA group, respectively (p< 0.05). Conclusions: Conventional physical therapy plus the Mulligan's joint mobilization technique and acupuncture resulted in shorter treatment duration and higher WAADL and Treatment success scores in patients with shoulder pain.